Corporate social responsibility, organisational reputation and liability of foreignness - Yuting Zhang (South African Journal of Business Management, 2021)
Purpose: This study aimed to test the impact of corporate social responsibility (CSR) and its subdivision dimensions on the liability of foreignness (LOF), as well as the mediating effect of organisational reputation.